Talent Management Implementation Study at The Supreme Court of The Republic of Indonesia in The Era of Digital Transformation - Al Wafiroh, Nur Baity; Nurhaeni, Ismi Dwi Astuti; Haryanti, Rina Herlina (Universitas Muhammadiyah Gorontalo, 2025)
Digital transformation necessitates reform in talent management within the public sector, including the Supreme Court of the Republic of Indonesia/ Mahkamah Agung (MA RI). Although various digital systems have been implemented, their effectiveness has not been optimal due to a gap between policy design and implementation. This research aims to analyze the implementation of talent management in MA RI in the era of digital transformation. Using a qualitative approach and descriptive design, data were obtained through interviews, participatory observations, and documentation studies. The study's results indicate that uneven communication, human resource readiness that needs improvement, and limited digital system integration are the primary obstacles. The executive disposition that still relies on structural authority and complex bureaucratic structures also slows down the decision-making and coordination process between units. This study concludes that the success of digital talent management requires synergy between continuous training, strengthening technology infrastructure, and simplifying organizational structures. The limitation of this research lies in the scope of the institution which only includes the Supreme Court of the Republic of Indonesia, so the generalization of the results is limited. Further research is suggested to explore the long-term influence of digitalization of talent management on employee performance and institutional effectiveness, as well as how adaptation of bureaucratic structures can strengthen digital transformation in the public sector.